Historical and Cultural Landscapes: Challenges and Opportunities for Sustainable Tourism (Svaneti Example) - Maia Bliadze (Scientific Research and Experimental Development, 2026)
Historical and cultural landscapes are the result of a long-term interaction between humans and the natural environment and represent an important resource for the development of sustainable tourism. They combine cultural heritage, spatial identity and socio-economic potential. At the same time, the growth of tourism often poses serious threats to the authenticity and ecological sustainability of these landscapes. The article aims to analyze the role of historical and cultural landscapes in sustainable tourism, identify existing challenges and discuss development opportunities in the context of international and local experience.